2013
DOI: 10.1371/journal.pone.0061003
|View full text |Cite
|
Sign up to set email alerts
|

Sequence Analysis of 96 Genomic Regions Identifies Distinct Evolutionary Lineages within CC156, the Largest Streptococcus pneumoniae Clonal Complex in the MLST Database

Abstract: Multi-Locus Sequence Typing (MLST) of Streptococcus pneumoniae is based on the sequence of seven housekeeping gene fragments. The analysis of MLST allelic profiles by eBURST allows the grouping of genetically related strains into Clonal Complexes (CCs) including those genotypes with a common descent from a predicted ancestor. However, the increasing use of MLST to characterize S. pneumoniae strains has led to the identification of a large number of new Sequence Types (STs) causing the merger of formerly distin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…In total, 47 STs were detected, clustered in 20 CCs and 2 singleton groups (Table 4). The most abundant CC was CC156, which included 7 STs clustered in different genetic lineages [22] and multiple serotypes (6B, 6C, 14, 19F, 23B, and 24F). The second most abundant CC was CC315, which included PMEN clone Poland 6B -20/ST315 and comprised only serotype 6C isolates, followed by CC230, which included Denmark 14 -32/ST230 and was composed of serotypes 19A and 24F.…”
Section: Resultsmentioning
confidence: 99%
“…In total, 47 STs were detected, clustered in 20 CCs and 2 singleton groups (Table 4). The most abundant CC was CC156, which included 7 STs clustered in different genetic lineages [22] and multiple serotypes (6B, 6C, 14, 19F, 23B, and 24F). The second most abundant CC was CC315, which included PMEN clone Poland 6B -20/ST315 and comprised only serotype 6C isolates, followed by CC230, which included Denmark 14 -32/ST230 and was composed of serotypes 19A and 24F.…”
Section: Resultsmentioning
confidence: 99%
“…During the study period CC156 accounted for an approximately constant proportion of the characterized isolates in each year (varying slightly between 5.5% and 7.0%). The observed persistence of this CC may be explained by three different factors: 1) while it is true that PCV7 serotypes have declined in importance, it is also true that they still account for approximately one fifth of adult IPD and 57% of the isolates expressing PCV7 serotypes in 2008–2011 belonged to this CC; 2) this CC is strongly associated with antimicrobial resistance, with n = 70/101 isolates being resistant to at least two different classes of antibiotics; and 3) the genomic diversity of CC156 is high, with one study reporting the presence of 10 unrelated genetic subgroups [ 22 ], suggesting that this CC may be particularly suited to adapt to different selective pressures. Regarding the last point, in our study we found representatives of three different clones recognized by the PMEN included in CC156: Spain 9V -156, Colombia 23F -338 and Greece 6B -273 [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the giant CC156 surfogroup, whose size is a consequence of eBURST clustering collapse, reached a mere 40% surfogroup homogeneity. Meanwhile, the CC156 lineages derived from MLST-96 technique (Moschioni et al, 2013 ) are reasonably associated with different surfogroups.…”
Section: Discussionmentioning
confidence: 99%
“…Both STs are grouped into clonal complex CC180, considering ST180 as the founder. However, intra-clonal variability associated with clinical behavior, e.g., local outbreaks, does exist (Silva et al, 2006 ; Moschioni et al, 2013 ). Subclones can emerge either from point mutations, deletions/duplications of key genes, or prophage integrations.…”
Section: Introductionmentioning
confidence: 99%